2022
DOI: 10.1093/jn/nxac141
|View full text |Cite
|
Sign up to set email alerts
|

Selenium-Enriched Cardamine violifolia Increases Selenium and Decreases Cholesterol Concentrations in Liver and Pectoral Muscle of Broilers

Abstract: Background Superanutriton of selenium (Se) in an effort to produce Se-enriched meat may inadvertently cause lipid accumulation. Se-enriched Cardamine violifolia (SeCv) contains over 80% of Se in organic forms. Objective This study was to determine whether feeding chickens a high dose of SeCv could produce Se-biofortified muscle without altering their lipid metabolism. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 49 publications
0
1
0
Order By: Relevance
“…Therefore, the increased concentration of TG and TC in the livers of broilers exposed to HS may be due to abnormal lipid metabolism. A previous study reported that Se supplementation affects liver lipid metabolism and decreases cholesterol concentration in the livers of broilers [20]. In our study, all of the supplemented four Se sources consistently reduced liver TC levels, indicating that Se supplementation contributes to the improvement of lipid metabolism disorders in the livers of broilers exposed to HS.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Therefore, the increased concentration of TG and TC in the livers of broilers exposed to HS may be due to abnormal lipid metabolism. A previous study reported that Se supplementation affects liver lipid metabolism and decreases cholesterol concentration in the livers of broilers [20]. In our study, all of the supplemented four Se sources consistently reduced liver TC levels, indicating that Se supplementation contributes to the improvement of lipid metabolism disorders in the livers of broilers exposed to HS.…”
Section: Discussionsupporting
confidence: 76%
“…At present, 24 selenoproteins have been identified in poultry [19]. Studies suggest that dietary Se supplementation is involved in hepatic lipid metabolism by regulating the expression of selenoproteins [20][21][22]. Evidence indicates that ER resident selenoproteins contribute to the maintenance of ER homeostasis [23].…”
Section: Introductionmentioning
confidence: 99%
“…Also, mortality was recorded throughout the trial [ 22 ]. Two birds with a close average body weight were selected from each replicate to be weighed and euthanized weekly [ 23 ]. The carcasses and feathers were separated, weighed, and collected to determine the protein deposition and amino acid pattern.…”
Section: Methodsmentioning
confidence: 99%
“…Selenium is considered an essential micronutrient that should be supplied in aquafeed for optimal growth and physiological function [7]. Selenium deficiency can induce multiple tissue damage with dysregulation of immune and redox homeostasis under heat stress [8]. Using nanoparticles in fish feed formulations has recently gained considerable attention because it offers unique methods for increasing bioavailability, safety, and absorption in aquaculture [9].…”
Section: Introductionmentioning
confidence: 99%